A construction grammar approach to the innovative use of [unless x] - Mendes Junior, Wellington; Mattos, Elisa (The ESPecialist, 2024)
This study analyzes the construction [unless X] as based on the Construction Grammar framework (cf. Fillmore et al., 1988; Goldberg, 1995, 2006; Bybee, 2010), in association with the Corpus Linguistics (McEnery; Hardie, 2013; Sinclair, 2005) methodology. The construction [unless X] characterizes as an innovative use of the word “unless”, in which the conjunction isn’t followed by a subordinate clause, as it can be seen in “don’t add Coca Cola unless diet” or “he was so calm unless tried” or “I can never tell the season unless winter”. Motivated by the findings of Mendes Junior and Mattos (2021), who reported high rates of productivity in the construction [because X] (e.g. “I’m excited for my holidays because tired”), we propose a model that accounts for the new constructional properties of “unless”. Data were collected through the iWeb Corpus (Davies, 2018), which contains 14 billion words extracted from about 22 million web pages. Preliminary analysis shows that the construction [unless X] heavily favors verbs in the past participle, adjectives, adverbs and nouns in the [X] slot. Moreover, the [X] slot cannot be filled by interjections, pronouns, conjunctions and prepositions, as opposed to [because X]. Following Fillmore et al. (1988), [unless X] can be understood as codable, formal, extra-grammatical construction. We suggest that [unless X] often behaves similarly to the traditional use of ‘unless’, though it tends to favor reduced clauses and is mainly used in more informal contexts.